The expression of protoporphyrinogen oxidase IN HUMAN TISSUES - Corrigall, A V; Campbell, J A H; Siziba, K; Kirsch, R E; Meissner, P N (Cellular and Molecular Biology, 2009)
Protoporphyrinogen oxidase is the penultimate enzyme in the haem biosynthetic pathway. In this study, the expression of protoporphyrinogen oxidase in a variety of human organs has been documented by immunohistochemical means at the light microscopy level in order to shed light on its inter- and intra-organ distribution. The expression varied amongst organs and the various cell types within an organ. The pattern of staining generally reflected presumed metabolic functionality and haem demand. Strongest staining was noted in hepatocytes, proximal convoluted tubules of the kidney, serous cells of the peribronchial gland in the lung, parietal cells of the stomach, tips of the villi in the small intestine and interstitial cells of the testis. Our results suggest that there are some significant sites of haem synthesis in addition to the liver and bone marrow, and should be borne in mind in studies related to haem or porphyrin dynamics and flux.